CONSTRUCTIONS OF CIVIL BUILDINGS - SH.A. Egamberdiyeva (Galaxy International Interdisciplinary Research Journal, 2024)
This article is on the topic of constructions of civil buildings, it contains detailed information about the structural elements that make up civil buildings and their place in construction.